MANAGEMENT AND OUTCOMES OF ACUTE MYOCARDIAL INFARCTION IN MAYO HOSPITAL: A RETROSPECTIVE STUDY (The Research of Medical Science Review, 2025)
Introduction: AMI is still considered as a major public health problem with significant morbidity and mortality in the global population. The health facility managers have the responsibility of developing sound managerial practices since patient outcomes depend on them. The present research aims to assess the management and results of Acute Myocardial Infarction at Mayo Hospital in Lahore. Objectives: To compare different treatment strategies of subjects with AMI, patients’ characteristics and outcomes by using variables that predict prognosis. Materials and Methods: This cross-sectional study was carried out at Mayo Hospital Lahore from January 2024 to June 2024. The patients’ characteristics, such as age, sex, co-morbidities, treatments given, and the patient’s outcomes, were recorded and evaluated. The inclusion criteria included all the patients diagnosed with AMI, while the exclusion criteria included patients with partial data, patients without AMI diagnosis, and patients with noncardiac diseases. Results: Percutaneous coronary intervention (PCI) was also similarly efficient, with improved survival rates compared to the other methods. Diabetes or hypertension and thus affect the prognosis of the disease. The patients with cardiogenic shock had higher mortality rates than any of the other groups of patients. Conclusion: AMI management should comprise the early interventions, guideline-directed medical therapy, and comprehensive risk management to enhance its outcomes.